Repair of Exposed Ahmed Glaucoma Valve Tubes: Long-term Outcomes. Issue 6 (June 2018) - Einan-Lifshitz, Adi; Belkin, Avner; Mathew, David; Sorkin, Nir; Chan, Clara C.; Buys, Yvonne M.; Trope, Graham E.; Rootman, David S.
Abstract : Purpose: To assess the long-term outcomes of glaucoma drainage device (GDD) exposure repair with corneal lamellar patch graft covered by a buccal mucous membrane graft sutured to surrounding conjunctiva. Methods: In this retrospective longitudinal study, the charts of all patients who underwent buccal mucous membrane grafts combined with corneal lamellar patch grafts for exposed GDD tubes between the years 2006 to 2013 were reviewed. A minimum follow-up of 3 years was required for inclusion. Primary outcomes were categorized as complete success: adequate coverage throughout the study period without further intervention after 1 repair; qualified success: adequate coverage despite minor additional procedures (eg, suturing); failure: re-erosion of the GDD tube. Results: A total of 23 tube exposures were included. Average time from GDD insertion to first erosion was 54.0±38.9 months (range, 5 to 120). Complete success was achieved in 19 cases (82.6%), and qualified success in 1 case (4.3%). There were 3 failures (13.1%). Overall success (complete+qualified) after 1 or 2 buccal mucous membrane graft repairs was achieved in 22 of 23 cases (95.7%). Average follow-up time for the successful cases (complete+qualified) was 69.5±25.4 months (median, 72.5; range, 36 to 124). There was no difference in time to first erosion between the success (complete+qualified) and failure groups: 53.8±38.3 months (range, 5 to 120) and 62.3±51.6 months (range, 5 to 105), respectively ( P =0.78). Conclusions: Buccal mucous membrane grafts in combination with a lamellar corneal patch graft is a viable surgical strategy for eroded GDDs, providing good long-term outcomes; however, later interventions may be needed.